Translation Shift in English-Indonesian Translation of “The Things You Can See Only When You Slow Down” - I Gusti Ayu Mahatma Agung; Ni Wayan Suastini (Universitas Veteran Bangun Nusantara, 2022)
This study aims to analyze the types of shift in the translation of the book “The Things You Can See Only When You Slow Down” by Haemin Sunim. The qualitative method was employed in this study. The data was collected through document analysis. Following the data collection procedure, the data were categorized and analyzed using the theories proposed by Catford (1965) and Machali (2009). The result shows that there are six types of shifts found in the translation of the book. They are level shift, structure shift, class shift, unit shift, intra-system shift, and meaning shift. Unit shift was the most prevalent translation shift, followed by class shift. There are cases of obligatory shifts due to different linguistic systems of the source language and the target language. In such contexts, the shifts are necessary to achieve accuracy and acceptability in the target language. In addition, there are also optional shifts due to the translator’s preference or different cultural backgrounds. It is applied to increase the readability in the target language.